A sigma factor RpoD negatively regulates temperature-dependent metalloprotease expression in a pathogenic Vibrio splendidus. (March 2019) - Zhang, Chi; Zhang, Weiwei; Liang, Weikang; Shao, Yina; Zhao, Xuelin; Li, Chenghua
Abstract: Vibrio splendidus is an important aquatic pathogen that can cause typical symptoms of skin ulceration syndrome (SUS) in sea cucumber Apostichopus japonicus . A metalloprotease Vsm from V. splendidus, has been reported to be an important virulence factor for SUS outbreak. In the present study, the mRNA expression level of vsm was found to correlate to temperature with a peak expression at 28 °C. In contrast, the expression of a sigma factor rpoD, was significantly repressed at 28 °C. A predicted RpoD binding site in the promoter region of vsm revealed the potential regulation of RpoD on vsm expression. Electrophoretic mobility shift assay showed that the purified recombinant RpoD could specifically bind to the promoter region of vsm . Co-transfection of vsm promotor and pT3-rpoD into E. coli significantly inhibited the β -Galactosidase activities in a temperature-dependent manner, and the activities were 0.41-, 0.89- and 0.18-fold at 10 °C, 28 °C and 37 °C compared to the control DH5α/pT3. A rpoD overexpression strain Vs/JRTcrpoD was constructed to further examine the effect of RpoD on the expression of vsm in vivo . By real time RT-PCR analysis, vsm expression level was 0.47-fold in Vs/JRTcrpoD compared to that in Vs/JRTc. Consistently, the metalloprotease activities in Vs/JRTcrpoD was decreased by 18% compared to that in Vs/JRTc. All the results suggested that the sigma factor RpoD, showed a negative regulation on expression of vsm gene by directly interacting with the promoter region of vsm . Highlights: The mRNA levels of Vsm and a sigma factor of RpoD were dependent on temperature. Electrophoretic mobility shift assay showed that the purified recombinant RpoD could bind to the promoter region of Vsm. The plasmids pT3-RpoD transformed into E.coil /P vsm -pSC11 significantly inhibited the β -Galactosidase activities. A RpoD overexpression strain Vs/JRTc RpoD could significantly inhibit the mRNA and activities of Vsm.